Reducing Academic Procrastination in Students Through Individual Counseling with Cognitive Restructuring Techniques: A Case Study at Pondok Pesantren Al-Hikmah Bandar Lampung - Lestari, Hani; Mawarni, Anisa; Ratsameemonthon, Chadchom (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2024)
This study aims to understand how individual counseling using cognitive restructuring techniques can reduce academic procrastination behaviors among students at Pondok Pesantren Al-Hikmah Bandar Lampung. The research employs a descriptive qualitative method, where the researcher observes and interacts with the students. The study focuses on four students, two boys and two girls, who have issues with academic procrastination, selected through purposive sampling. Data collection techniques used in this research include observation, interviews, and documentation. The results indicate that individual counseling with cognitive restructuring techniques significantly impacts reducing academic procrastination behaviors among the students at Pondok Pesantren Al-Hikmah Bandar Lampung. The counseling sessions helped the students realize that academic procrastination can lead to anxiety, fear, and worry. After participating in the counseling sessions, the four students recognized their mistakes and are now committed to improving their behaviors.